Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Select the correct answer.

What are the [tex]\(x\)[/tex]- and [tex]\(y\)[/tex]-intercepts of the function [tex]\(g(x)=(x+1)\left(x^2-10x+24\right)\)[/tex]?

A. [tex]\(x\)[/tex]-intercepts: [tex]\(-1, 4, 6\)[/tex]; [tex]\(y\)[/tex]-intercept: 24

B. [tex]\(x\)[/tex]-intercepts: [tex]\(-6, -4, 1\)[/tex]; [tex]\(y\)[/tex]-intercept: 24

C. [tex]\(x\)[/tex]-intercepts: [tex]\(-4, -1, 6\)[/tex]; [tex]\(y\)[/tex]-intercept: -24

D. [tex]\(x\)[/tex]-intercepts: [tex]\(-6, -1, 4\)[/tex]; [tex]\(y\)[/tex]-intercept: -24


Sagot :

To find the [tex]$x$[/tex]-intercepts and [tex]$y$[/tex]-intercept of the function [tex]\( g(x) = (x+1)(x^2 - 10x + 24) \)[/tex], let's proceed with a step-by-step solution.

Step 1: Finding the [tex]$x$[/tex]-intercepts

The [tex]$x$[/tex]-intercepts occur where [tex]\( g(x) = 0 \)[/tex]. So, we need to solve the equation:
[tex]\[ (x + 1)(x^2 - 10x + 24) = 0 \][/tex]

This equation is satisfied when either factor is zero:
[tex]\[ x + 1 = 0 \quad \text{or} \quad x^2 - 10x + 24 = 0 \][/tex]

Solving [tex]\( x + 1 = 0 \)[/tex]:
[tex]\[ x = -1 \][/tex]

Now, solving the quadratic equation [tex]\( x^2 - 10x + 24 = 0 \)[/tex], we can use the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -10 \)[/tex], and [tex]\( c = 24 \)[/tex]:
[tex]\[ x = \frac{-(-10) \pm \sqrt{(-10)^2 - 4 \cdot 1 \cdot 24}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{10 \pm \sqrt{100 - 96}}{2} \][/tex]
[tex]\[ x = \frac{10 \pm \sqrt{4}}{2} \][/tex]
[tex]\[ x = \frac{10 \pm 2}{2} \][/tex]

This gives us two solutions:
[tex]\[ x = \frac{10 + 2}{2} = 6 \][/tex]
[tex]\[ x = \frac{10 - 2}{2} = 4 \][/tex]

So, the [tex]\( x \)[/tex]-intercepts are [tex]\( x = -1, 4, 6 \)[/tex].

Step 2: Finding the [tex]$y$[/tex]-intercept

The [tex]$y$[/tex]-intercept occurs where [tex]\( x = 0 \)[/tex]. We find [tex]\( g(0) \)[/tex]:
[tex]\[ g(0) = (0+1)(0^2 - 10 \cdot 0 + 24) \][/tex]
[tex]\[ g(0) = 1 \cdot 24 = 24 \][/tex]

So, the [tex]\( y \)[/tex]-intercept is [tex]\( 24 \)[/tex].

Step 3: Conclusion

The [tex]$x$[/tex]-intercepts are [tex]\( -1, 4, 6 \)[/tex] and the [tex]$y$[/tex]-intercept is [tex]\( 24 \)[/tex].

By analyzing the options provided in the question:

A. [tex]$x$[/tex]-intercepts: [tex]$-1, 4, 6$[/tex]; [tex]$y$[/tex]-intercept: 24
B. [tex]$x$[/tex]-intercepts: [tex]$-6, -4$[/tex], and [tex]$1$[/tex]; [tex]$y$[/tex]-intercept: 24
C. [tex]$x$[/tex]-intercepts: [tex]$-4, -1, 6$[/tex]; [tex]$y$[/tex]-intercept: -24
D. [tex]$x$[/tex]-intercepts: [tex]$-6, -1, 4$[/tex]; [tex]$y$[/tex]-intercept: -24

The correct answer is:
A. [tex]$x$[/tex]-intercepts: [tex]$-1, 4, 6$[/tex]; [tex]$y$[/tex]-intercept: 24
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.